Carbon composite thermoplastic electrodes integrated with mini-printed circuit board for wireless detection of calcium ions - Ozer, Tugba (SPRINGERNATURE, 2022)
Here, a smartphone-based portable sensing system is developed for real-time detection of Ca2+ ions in a variety of biofluids. A solid-contact calcium-selective electrode (Ca2+-ISE) consisting of an ion-selective membrane (ISM), carbon black nanomaterial and polystyrene-graphite nanoplatelets as a solid contact was fabricated. The polyvinylchloride (PVC)-based ISM was optimized using different plasticizers and ion-exchangers. Under optimized conditions, the solid contacts were electrochemically characterized by electrochemical impedance spectroscopy (EIS), chronopotentiometric and potentiometric measurements. The Ca2+-ISE showed a Nernst response with a slope of 31.2 +/- 0.6 mV/decade in the concentration range from 0.1 M to 10(-4) M Ca2+ with a limit of detection (LOD) of 1.0 x 10(-5) M. In addition, the ISEs exhibited good selectivity to Ca2+ ions over various interfering electrolytes and metabolites. The Ca2+-ISEs were applied in human urine and, artificial serum and cerebrospinal fluid samples. The ISEs showed good recoveries between 90 and 105%, indicating potential applicability of these electrodes in biological fluids. The portable lab-made potentiometer provides wireless data signaling and transmission to a smartphone and final Ca2+ concentration display due to its customized software. Therefore, the developed smartphone-based sensing platform offers low cost (< $25), rapid, user-friendly detection of Ca2+ especially in resource-limited areas.
Keywords: Ion-selective electrode; Point-of-care; Calcium; Wireless detection; Nanomaterial; 3D printing; SELECTIVE ELECTRODES; MAGNESIUM; MEMBRANE; SENSORS; Chemistry